Sleep and circadian rhythm disruption alters the lung transcriptome to predispose to viral infection - Taylor, L; Von Lendenfeld, F; Ashton, A; Sanghani, H; Di Pretoro, S; Usselmann, L; Veretennikova, M; Dallmann, R; McKeating, JA; Vasudevan, S; Jagannath, A (Cell Press, 2023)
Sleep and circadian rhythm disruption (SCRD), as encountered during shift work, increases the risk of respiratory viral infection including SARS-CoV-2. However, the mechanism(s) underpinning higher rates of respiratory viral infection following SCRD remain poorly characterized. To address this, we investigated the effects of acute sleep deprivation on the mouse lung transcriptome. Here we show that sleep deprivation profoundly alters the transcriptional landscape of the lung, causing the suppression of both innate and adaptive immune systems, disrupting the circadian clock, and activating genes implicated in SARS-CoV-2 replication, thereby generating a lung environment that could promote viral infection and associated disease pathogenesis. Our study provides a mechanistic explanation of how SCRD increases the risk of respiratory viral infections including SARS-CoV-2 and highlights possible therapeutic avenues for the prevention and treatment of respiratory viral infection.